Enhancing research methodologies in the built environment & engineering volume 2: project design & sustainability / Hamimah Adnan ... [et al.] - Adnan, Hamimah; Alias, Zarina; Salleh, Siti Aekbal; Yaman, Rostam; Bakri, Aidatul Fadzlin; Esa, Mohd Reza; Bakhary, Nor Azmi; Khaderi, Shamsida Saidan; Mohd Yussof, Farrah Norizzah; Mohamad Yusawan, Norazian (UiTM Press, 2013)
Increasingly, parks and protected areas are seen as tourist locations that could help visitors learn and experience a particular place. The uniqueness of a successful park is derived not only from the value of the resources available but also on how well those values are exhibited and presented to tourist. The first impression account is believed to have a significant impact on one's recreational experience. A group of Malaysian students on an exchange program at the University of South Australia evaluated several parks and recreation areas in Adelaide, South Australia. Using mainly observational investigation with background research on interpretation, the study surveyed four different types of parks around the city. Focus on theme, media and facility the research analysed the park attributes on interpretations approaches based on their strengths and potential. The result found several successful methods employed for helping tourist gain valuable experience in their visits.